Review of the leafhopper genus Hatigoria Distant with one new species (Hemiptera: Cicadellidae: Hylicinae) - Tang, Jiu; Zhang, Yalin (Zootaxa, 2021)
The taxonomy of the hylicine genus Hatigoria Distant is reviewed based on morphological study of the types and other specimens. The male external morphology and genitalia of two known species, H. praeiens Distant, 1908 and H. sauteri Jacobi, 1914, are described and photographed for the first time. A description and figures of the female ovipositor of H. praeiens Distant, 1908 are provided. One new species, H. longistylia n. sp., from Laos and China is reported with descriptions and figures. This also represents the first record of the genus Hatigoria from Laos. A key to adult males of all species is provided.